Transmission dynamics, characterization, diagnosis, and control of Bovine Respiratory Disease - Capik, Sarah F. (Kansas State University, 2016)
The diagnosis and prevention of bovine respiratory disease (BRD) is challenging due to the multifactorial nature of the disease. Mannheimia haemolytica, Pasteurella multocida, and Histophilus somni are gram negative bacteria that are commonly considered three of the most important bacterial agents involved in the etiology of BRD; all three are also commensals in the upper respiratory tracts of healthy cattle. However, despite decades of study, questions still remain regarding the transmission dynamics and characterization of these bacteria, the ability of diagnostic sampling methods to accurately portray the causative bacteria, and ways to mitigate the effects of risk factors for BRD such as long-distance transportation. Through our research, we have demonstrated how variable the culture results of a single nasopharyngeal swab can be and the challenges of using an individual culture to truly represent animal M. haemolytica status. Additionally, comparison of the diagnostic performance of two antemortem sampling methods, nasopharyngeal swabs (NPS) and bronchoalveolar lavages (BAL), revealed high agreement, high negative predictive values of NPS for the presence of M. haemolytica, P. multocida, and H. somni in the lungs, and the potential for different susceptibility profiles from paired NPS and BAL samples. As agreement and predictive values can vary with disease prevalence, interpretation of diagnostic test results should be done carefully and with due consideration of the sample population in which the test is being applied. An investigation into cattle behavior following a relatively innocuous handling procedure indicated that some behaviors are altered after handling and restraint in a squeeze chute. Additionally, we demonstrated that cattle with different temperament scores may have different activity levels and spend different amounts of time within 1 m of the hay bunk, grain bunk, waterer, and shed after handling. Consequently, there is also the potential to improve upon disease detection algorithms by incorporating behavioral changes that may occur after handling events and the need for careful trial design when behavioral parameters are a trial outcome. Additionally, this study indicated that some behaviors may vary for calves that react differently when handled, which also has potential implications when behavior is considered a variable of interest. Examination of the potential for 1 mg/kg oral meloxicam administered pre-transport to mitigate the effects of long-distance transportation revealed that meloxicam did not have a statistically significant effect on the maintenance of leukocyte function or the reduction of inflammation during or after long-distance transportation in healthy steers. Finally, a report on two separate experiments regarding the effects of 1 mg/kg oral meloxicam administered pre-transport on the movement, feeding, and drinking behaviors and performance of transported and non-transported calves demonstrated that there was a significant day effect on behaviors in transported calves but meloxicam did not affect behavior or performance. However, meloxicam did modify the effect of day on daily distance traveled in non-transported calves but there were no significant within-day comparisons between non-transported meloxicam and non-transported control calves. These results do not provide evidence for the benefit of administering a single dose of 1 mg/kg oral meloxicam prior to long-distance transportation.
Keywords: Bovine respiratory disease; Cattle; Mannheimia haemolytica; Behavior; Stress; Transportation